Pengembangan E-Modul Ajar Kurikulum Merdeka Berbasis Augmented Reality pada Mata Pelajaran TIK (Teknologi Informasi dan Komunikasi) kelas VII UPT SMP Negeri 4 Parepare - Andayani, Dyah Darma; Fathahillah; Jakob, Fidela Evania (P3M POLITEKNIK NEGERI AMBON, 2024)
This research aims to develop and determine the feasibility of E-Modules in ICT (Information and Communication Technology) subjects in class VII UPT SMP Negeri 4 Parepare. The type of research used is Research and Development (R&D), which is one of the development methods used to produce products or test the feasibility of the product. The development model in this research is the 4D (Four-D) model which consists of 4 development stages including Definition, Planning, Development and Dissemination. This development research used a trial sample of 32 active students in class VII.3. The data analysis technique used is Descriptive Statistics technique. In the feasibility trial, material experts got a result of 95% in the